Unbalanced Occlusion Modifies the Pattern of Brain Activity During Execution of a Finger to Thumb Motor Task - Tramonti Fantozzi, Maria Paola; Diciotti, Stefano; Tessa, Carlo; Castagna, Barbara; Chiesa, Daniele; Barresi, Massimo; Ravenna, Giulio; Faraguna, Ugo; Vignali, Claudio; De Cicco, Vincenzo; Manzoni, Diego (Frontiers in Neuroscience, 2019)
In order to assess possible influences of occlusion on motor performance, we studied by functional magnetic resonance imaging (fMRI) the changes in the blood oxygenation level dependent (BOLD) signal induced at brain level by a finger to thumb motor task in a population of subjects characterized by an asymmetric activation of jaw muscles during clenching (malocclusion). In these subjects, appropriate occlusal correction by an oral orthotic (bite) reduced the masticatory asymmetry. The finger to thumb task was performed while the subject’s dental arches were touching, in two conditions: a) with the teeth in direct contact (Bite OFF) and b) with the bite interposed between the arches (Bite ON). Both conditions required only a very slight activation of masticatory muscles. Maps of the BOLD signal recorded during the movement were contrasted with the resting condition (activation maps). Areas of increased BOLD signal in the activation maps were observed bilaterally, being larger in Bite OFF than Bite ON. These areas included the sensorimotor cortex, the supplementary-premotor cortex, the cerebellum and the left inferior frontal gyrus (Broca’s area). Between conditions comparison of the activation maps (Bite OFF/Bite ON) showed that, in Bite OFF, the BOLD signal was significantly higher at the level of the trigeminal sensorimotor region, the premotor cortex, the cerebellum, the parietal, temporal, occipital and limbic regions (bilaterally) as well as within the left Broca’s area. These data are consistent with the hypothesis that malocclusion makes movement performance more difficult, requiring a stronger activation of the Broca’s area, which participate in planning of the motor sequence, and of the cerebellum, which is essential in motor coordination. Moreover, malocclusion leads to a higher spread of activation in motor regions not directly involved in the control of the moving body parts and generates an higher engagement of regions involved in visuo-spatial and temporal processing, as well as in the control of cognitive activities and alertness levels.